Neutrinos and electromagnetic gauge invariance - Pisano, F.; SilvaSobrinho, J. A.; Tonasse, M. D. (Elsevier B.V., 1996)
We examine a recently proposed connection constraining U(1)(em) electromagnetic gauge invariance and the nature of neutrino mass terms in the framework of G(0) = SU(3)(C) x G(W) x U(1)(N) gauge extensions of the standard model where G(W) denotes the weak isospin special unitary extended groups. We show that in a large class of G(0) models there is a unique fermion representation content and scalar fields which select the neutrino mass terms. Noteworthy. even though there are mathematically equivalent representation contents then can be different aspects concerning the physical consequences which are not a mere truism.